Early Warning Indicators of Severe COVID-19: A Single-Center Study of Cases From Shanghai, China - Lu, Yiming; Sun, Kuo; Guo, Shanshan; Wang, Junjie; Li, An; Rong, Xuli; Wang, Tingfang; Shang, Yan; Chang, Wenjun; Wang, Sheng (Frontiers in Medicine, 2020)
Abstract Background: Patients with severe novel coronavirus disease (COVID-19) can likely develop comorbidities, which can lead to irreversible organ damage and, eventually, death. However, early indicators of disease progression remain unclear. This study aimed to identify early indicators of disease progression to provide a basis for improved prognostic prediction and disease management. Methods: We evaluated 53 recovered adult COVID-19 patients who were treated at Shanghai Public Health Clinical Center between January 20, 2020, and February 20, 2020. The patients were categorized into the following four groups according to their condition upon admission: mild condition (n=3), moderate (n=41), severe (n=7), and critical (n=2). They were also categorized according to disease progression as mild or moderate conditions that remained stable (n=26), moderate disease that progressed to severe condition (n=18), and continuously severe or critical (n=9). We then focus on investigating the differences in the epidemiological and laboratory indicators between remained stable COVID-19 cases and progressed to severe condition cases. Results: Mild or moderate patients were younger than severe or critical patients. The number of patients with shortness of breath and underlying diabetes and heart disease upon admission was higher in the severe or critical group. This group also showed considerably lower or higher values in 28 laboratory indicators. In addition, mild and moderate patients who remained stable were younger than moderate patients progressing to severe disease . Men had a higher risk of disease progression. Patients who progressed had either higher or lower values in 11 laboratory indicators. Survival curve analysis showed that age, procalcitonin, D-dimer, serum C-reactive protein, lactate dehydrogenase, lymphocytes, neutrophils, CD4%, and CD4/CD8 ratio were significant predictors of progression to severe disease. Conclusions: Lactate dehydrogenase and procalcitonin etc. are early warning indicators to severe COVID-19. Age (>64), Shortness of breath, past histories of diabetes and heart disease, and abnormality in 28 other indicators upon admission are indicative of severe or progression toward severe COVID-19. Meanwhile, abnormalities in 11 indicators and an abnormal coagulation function index upon admission are risk factors of progression to severe disease.